INCIDENCE, OUTCOME, AND MORTALITY PROFILE OF SOLID ORGAN INJURIES AMONG PATIENTS WITH BLUNT ABDOMINAL TRAUMA IN A TERTIARY CARE HOSPITAL: A PROSPECTIVE STUDY - Singh, Neetu; Kumar, Samridh; Khadda, Sandeep; ML, Dawan (Asian Journal of Pharmaceutical and Clinical Research, 2023)
Objective: The objective is to evaluate the histopathology and establish a correlation between placental changes in hypertensive disorders of pregnancy and fetal outcome. To access the solid organ injuries in blunt trauma abdomen patients with respect to management and outcome in a tertiary care hospital. Methods: A prospective descriptive type of study was conducted in a tertiary care hospital including 100 study participants from December 2021 to November 2022. All the patients with the diagnosis of the blunt abdominal trauma were assessed clinically at the time of presentation. After obtaining written informed consent, the detailed information regarding the mode of injury, clinical presentation was collected and recorded. Records were maintained about nonoperative and operative management duration of stay and outcome of patients. The data collected were then entered into MS Excel sheet and analyzed using SPSS v20.0. The data were presented in the form of numbers and proportions. Results and Conclusion: 76% of study participants reported to hospital within 6 h of trauma. 83% of patients had undergone conservative management, while 13% were managed surgically. The mortality rate among study participants was 5%.